A conceptual multilevel transmission framework linking enterprise management to economic efficiency and macroeconomic stability - Aliyeva, L.; Алієва, Л. А. (Харківський національний автомобільно-дорожній університет, 2026)
This study develops a multilevel management-driven conceptual framework explaining the hierarchical transmission of enterprise-level managerial capabilities into economic efficiency and macroeconomic stability. The research aims to systematize contemporary management approaches influencing firm performance and to substantiate a cumulative transmission model linking managerial systems, firm-level outcomes, sectoral dynamics, and macroeconomic indicators. The paper integrates strategic management, performance measurement systems, digital transformation, human capital development, and operational optimization into a coherent analytical architecture. A hierarchical cumulative transmission model is proposed, conceptualizing four interconnected levels: 1) managerial capabilities at the enterprise level; 2) measurable firmlevel economic outcomes, including productivity and capital efficiency; 3) sectoral aggregation effects; and 4) macroeconomic stability reflected in GDP growth, wage dynamics, and employment structures. The model emphasizes cumulative, lagged, conditional, and institutionally moderated effects, highlighting the non-linear nature of efficiency propagation across economic levels. Contextual analysis of official statistical data for Azerbaijan (2020–2025) indicates that wage growth, sectoral modernization, and productivity improvements can be interpreted as aggregated outcomes of enterprise-level managerial modernization and digital transformation. The findings confirm that sustainable macroeconomic stability depends not only on capital accumulation but also on the quality of strategic alignment, performance measurement, digital integration, and human capital management within firms. The proposed framework contributes to management and economic theory by formalizing the micro–macro linkage and offers practical implications for enterprises and policymakers aiming to strengthen long-term economic resilience and competitiveness.
Концептуальна багаторівнева трансмісійна модель, що поєднує управління підприємством з економічною ефективністю та макроекономічною стабільністю
Keywords: multilevel management framework; managerial capabilities; economic efficiency; digital transformation; labor productivity; macroeconomic stability; performance measurement systems; sectoral aggregation; багаторівнева управлінська модель; управлінські спроможності; економічна ефективність; цифрова трансформація; продуктивність праці; макроеко- номічна стабільність; системи вимірювання результативності; галузева агрегація; 005.21:330.34:330.101.541; 10.30977/ЕТК.2225-2304.2026.47.304